ADSORPTION OF FLUORIDE FROM INDUSTRIAL WASTEWATER IN FIXED BED COLUMN USING JAVA PLUM (SYZYGIUM CUMINI) - Singh, Tej Pratap; Ghosh, Sanjay; Cb, Majumder (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The quality of drinking water is important for public safety and quality of life. Thus, providing every person on earth safe drinking water seems to be the biggest challenge in front of mankind. For this purpose, here we have investigated the fluoride removal capacity of java plum. Methods: In this study, removal of fluoride from industrial wastewater using fixed-bed reactor adsorption techniques by java plum seed (Syzygium cumini) was investigated. Fixed-bed column experiments were carried out for different bed depths, influent fluoride concentrations, and various flow rates. The Thomas model and bed depth service time model were applied to the experimental results. Both model predictions verify the experimental data for all the process parameters studied, indicating that the models were suitable for java plum (S. cumini) seeds (Biosorbent) fix-bed column design. Results: The empty bed residence time (EBRT) model optimizes the EBRT, and the Thomas model showed that the adsorption capacity is strongly dependent on the flow rate, initial fluoride concentration, and bed depth and is greater under conditions of a lower concentration of fluoride, lower flow rate, and higher bed depth. Conclusion: The experimental results were encouraging and indicate that java plum (S. cumini) seed is a feasible option to use as a biosorbent to remove fluoride in a fixed bed adsorption process. Keywords: Adsorption, Column experiment, Thomas model, Empty bed residence time, Java plum.